KAJIAN TERJEMAHAN KALIMAT YANG MEREPRESENTASIKAN TINDAK TUTUR ASERTIF MENJAWAB DALAM DUA VERSI TERJEMAHAN NOVEL PRIDE AND PREJUDICE - Paramita Widya Hapsari; Nababan M.R.; Djatmika Djatmika (Prasasti: Journal of Linguistics, 2016)
This research is conducted by analyzing answering speech acts in Pride and Prejudice (PAP) novel and its two translation versions, Shira Media and Qanita Publisher. The aims of this research are to describe: (1) observing or non-observing the maxim, (2) the translation techniques used for translating answering speech acts in PAP novel and its two translation versions, (3) the translation quality of answering speech acts in PAP novel and its two translation versions, (4) the impacts of translation techniques toward the quality of answering speech acts in PAP novel.